Studies in the Measurements of Refractive Index of Substituted Thio-Carbamidonapthols In 100% & 90% Binary Mixtures of 70% Etoh-H2O Mixture at 298.15 K - Khan, S. R.; Lunge, M. S. Lunge; Tayade, D. T. (Asian Journal of Pharmaceutical Research and Development, 2024)
After synthesis of any chemical moiety; physico-chemical properties of that chemical moiety must be investigated. These are essential for predications of medicinal, agricultural, industrial, biochemical and biological applications theoretically and refractometric measurement is one of the best method for the determination of the same in the drug chemistry. Refractometric measurements of chemical moiety are one of the important study for understanding the pharmacokinetics study of synthesized or isolated chemical moiety. Considering all these things refractrometic measurements of 4-amino-1-naphthol [4-AN], 4-phenylthiocarbamido-1-naphthol [4-PTCN], 4-p-chlorophenylthiocarbamido-1-naphthol [4-p-CPTCN] and 4-p-tolylthiocarbamido-1-naphthol [4-p-TPTCN] have been carried out at 100% and 90%, binary mixtures of 70% ethanol-water mixtures in 0.002, 0.004, 0.006, 0.008 and 0.01M concentrations at 298.15K were successfully investigated and gave good results.